Globalised Islam: search for a new Ummah - Roy, Olivier (Delhi Rupa, 2005)
The search for a new Ummah world including Hamas of Palestine and Hezbollah of Lebanon and the uprooted militants who strive to establish an imaginary Ummah, or Muslim community, not attached to any particular society or territory. Roy provides a detailed comparison of three transnational movements, whether peaceful like Tablighi Jama'at and the Islamic brotherhoods, or violent, like Al Qaeda. He shows how neofundamentalism acknowledges without nostalgia the loss of pristine cultures identity that transcends the notion of culture. Thus contemporary Islamic fundamentalism is not a simple reaction against westernization but a product and an agent of the complex forces of globalization.
Keywords: Diasporas